A 2D metal–organic framework with dual‐acidic sites for the valorization of saccharides to 5‐hydroxymethylfurfural. Issue 2 (2nd September 2022) - Zhong, Yao; Huang, Cuiying; Cai, Jianxin; Wang, Jun; Zeng, Zheling; Deng, Qiang
Abstract: The conversion of macromolecular saccharides (fructose, glucose, sucrose, and inulin) to 5‐hydroxymethylfurfural (HMF) is often limited by the mass transfer resistance of existing catalysts. Herein, a two‐dimensional metal–organic framework (NUS‐8‐PhSO3 H) containing high densities of dual acidic sites (Lewis and Brønsted acid sites) was developed for the first time by diazo grafting. Characterization results and reaction kinetics showed that the rapid molecular diffusion leads to an unusual pseudozeroth reaction order and a considerably lower apparent activation energy for the fructose reaction over NUS‐8‐PhSO3 H in contrast to the first order and higher activation energy over three‐dimensional counterpart (NUS‐16‐PhSO3 H) and reported catalysts. In addition, NUS‐8‐PhSO3 H can also produce substantially high HMF yields and has a low activation energy for other saccharides (glucose, sucrose, and inulin) by powerful tandem steps, including polysaccharide hydrolysis, glucose isomerization, and fructose dehydration. The preparation of hydrophobic acidic NUS‐8‐PhSO3 H provides an efficient means of synthesizing HMF from various saccharides.